Analysis of Aggressive Behavior Studies in the Workplace in Indonesia: A Systematic Literature Review - Setyawan, Jefri; Agung Rian Asmoro (Community Medicine and Education Journal, 2024)
Aggressive behavior in the workplace is a crucial issue in Indonesia, potentially having a negative impact on individuals, teams, and organizations. This systematic literature review aims to analyze research on aggressive behavior in the workplace in Indonesia, including the factors that influence it, its impact, and coping strategies. This literature review uses the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) method. A literature search was conducted in electronic databases such as Google Scholar, Scopus, and PubMed with the keywords "aggressive behavior", "workplace", and "Indonesia". From 25 relevant studies, the findings show that the factors that influence aggressive behavior in the workplace in Indonesia include work stress, workload, interpersonal conflict, and organizational culture. The impact of aggressive behavior in the workplace can include reduced productivity, employee turnover, and poor mental health. Coping strategies that can be implemented to overcome aggressive behavior in the workplace include stress management training programs, conflict intervention programs, and the formation of a positive organizational culture. Aggressive behavior in the workplace is a complex problem with various factors that influence it. Comprehensive prevention and mitigation efforts are needed to overcome this problem and create a safe and conducive work environment.